Euler-Taylor Matrix Method for Solving Linear Volterra-Fredholm Integro-Differential Equations with Variable Coefficients: Teeranush Suebcharoen - Team, Support (Thai Journal of Mathematics, 2018)
In this paper, we present a numerical method for solving the high-order linear Volterra-Fredholm integro - differential equations with constant arguments and variable coefficients.The proposed method is based on the Euler polynomials and collocation points which transforms the integro - differential equation into a matrix equation.The matrix equation corresponds to a system of algebraic equations for which the unknown are Euler coefficients.Some examples are provided to illustrate the validity of the method.